An educational intervention to improve knowledge and attitudes to develop healthy dating relationships among undergraduates in Western Province - Eranga Fernando; Aindralal Balasuriya (College of Community Physicians of Sri Lanka, 2022)
Introduction Dating violence is a major public health issue which has failed to gain recognition in the country. It was never studied in the local setting despite the higher prevalence/ incidence reported in other countries. Objective To determine effectiveness of an educational intervention to improve knowledge and attitudes to develop healthy dating relationships among undergraduates in selected state universities in the Western Province. Methods This study was done as quasi-experimental study where an educational intervention was implemented to improve knowledge and attitudes to develop healthy dating relationships. Experimental and control groups were purposively selected from two different universities. The sample size calculated for each group was 65. Data was collected using a self-administered questionnaire at pre-intervention and six months post-intervention. The intervention comprised a lecture on "Dating relationships and dating violence" followed by discussions on case scenarios and a distribution of a booklet entitled "Healthy Relationships" among study participants. Control group was only given a lecture entitled "Time management, sexual and reproductive health and psychological well-being". Effectiveness of the intervention between groups was calculated using chi-square test and within the group improvement using McNemar test. Results Response rate was 91% (n=262/288) at the screening stage. There was a significant (p<0.0001) improvement in good knowledge on dating violence and in favourable attitudes (p=0.001) on dating violence, gender stereotypes and gender roles, in the experimental group compared to the control group at six months post-intervention. Conclusions and recommendations The educational intervention conducted proved to be effective in improving knowledge and attitudes. Recommend the application of educational intervention among the university students to reduce dating violence.